Performance Evaluation of a Simple Cluster-Based Aggregation and Routing in Wireless Sensor Networks - Sung-Hwa Hong; Jeong-Min Park; Joon-Min Gil (International Journal of Distributed Sensor Networks, 2013)
In future ubiquitous networks, sensor nodes should collect various environmental data and parameters. Because sensor nodes tend to have small and often irreplaceable batteries with limited power capacity, energy-efficient aggregation and routing are essential to achieve to a prolonged network lifetime. We propose a simple cluster-based data aggregation and routing algorithm (SCAR) that decreases the incurred overhead during the selection of cluster heads in wireless sensor networks. The performance results show that SCAR can prolong network lifetime via energy conservation and achieve energy-balancing when nodes are fixed or have limited mobility.